In vitro propagation and DNA barcode analysis of the endangered Silene schimperiana in Saint Katherine protectorate - Heba El-Sayed Ghareb; Shafik Darwish Ibrahim; Ghada Abd El-Moneim Hegazi (Journal of Genetic Engineering and Biotechnology, 2020)
Abstract Background Anthropogenic activity, climate change, pollution, and exploitation of natural resources are some reasons that cause threatening of plant diversity. Silene schimperiana is an endangered plant species in Egypt and is endemic to the high mountain of Saint Katherine Protected Area in southern Sinai. The purpose of the study was the ex situ conservation of Silene schimperiana through in vitro propagation and DNA barcode analysis. Results To develop an efficient ex situ conservation program of the plant, in vitro propagation protocol has been achieved from shoot tip and stem nodal segment explants of in vitro germinated seedlings. Explants were established in vitro on Murashige and Skoog (MS) medium supplemented with 2.89 μM gibberellic acid (GA3), 1.08 μM α-naphthaleneacetic acid (NAA), and 1.16 μM kinetin (Kin). The highest number of axillary shoots (9.27) was obtained when they were transferred to MS medium supplemented with 4.48 μM 6-benzyl adenine (BA). Hundred percent of multiple axillary shoots were rooted on quarter-strength MS medium supplemented with 4.92 μM indole-3-butyric acid (IBA) and 10.75 μM NAA. Rooted plants were transferred to pots containing a soil-peat mixture (1: 2 v/v) and successfully acclimatized in the greenhouse. Plant identification is a crucial aspect to understand and conserve plant diversity from extinction. DNA barcode analysis of Silene schimperiana was carried out using two chloroplast DNA markers (cpDNA): 1,5-bisphosphate carboxylase/oxygenase large subunit (rbcL) and RNA polymerase subunit (rpoC1) and a nuclear ribosome DNA marker (ncDNA), internal transcribed spacer (ITS). Phylogenetic analysis revealed a successful identification of Silene schimperiana on the species and genus levels and supported the inclusion of Silene schimperiana in genus Silene. Conclusions In this study, a relevant in vitro propagation method was established to facilitate the recovery of Silene schimperiana, in addition to DNA barcoding of the plant as a tool for effective management and conservation of plant genetic resources.